Thyrotoxicosis: What is the Cause in Our Population? Causes of Thyrotoxicosis - Ali, Ashfaq; Khan, Sulaiman; Anees, .; Hassan, Tariq; Mufti, Farah (Pakistan Journal of Health Sciences, 2025)
Thyrotoxicosis is an endocrine disorder in which excess amount of thyroid hormone is secreted in the blood stream and causes its action at the tissue level. Thyrotoxicosis highly affects the quality of life of patients suffering from the disease in carrying out daily activities. Proper treatment of thyrotoxicosis requires an accurate diagnosis. Objective: To determine the causes of thyrotoxicosis in patients reported for evaluation and management to specialized endocrine unit. Methods: This was a descriptive cross sectional observational study conducted by convenient sampling in Outpatient Department (Endocrinology Clinic) Khyber Pakhtunkhwa in six month’s duration (15th December 2023 to 15th May 2024) having sample size n=118. Thyrotoxicosis was labeled if patient has high T3, T4 (thyroxine and/or triiodothyronine) levels and suppressed thyroid stimulating hormones TSH levels. Information was gathered from the patients regarding their clinical signs and symptoms and anthropometrics. Laboratory investigations of thyroid function tests were obtained and analyzed. Results: The mean age of 118 patients was 40.39 ± 13.69 years, 28% male and 72% female patients were in enrolled in the study. Graves’ disease was most common form thyrotoxicosis making count of 50% of patients followed by toxic adenoma, toxic MNG, thyroiditis 16% and 14 % respectively. Anti-thyroid drugs count 43% of most of the patient’s treatment offered followed by radioactive iodine 28%. Conclusions: In conclusion, the main cause of thyrotoxicosis, includes grave’s disease, toxic adenoma and toxic MNG in Pakistani population. Thyrotoxicosis was more prevalent among female population as compared to males.